Bridging the Governance Gap: A Design Science Research Approach to Public Value-Driven Meso-Architecture in Indonesia’s Digital Government - Eka Putuasduki; Prasetyo Utomo (IJIES (International Journal of Innovation in Enterprise System), 2026)
Indonesia's transition from technocentric Electronic-Based Government System (SPBE) to Digital Government Architecture (PemDi) necessitates a paradigm shift toward Public Value Theory. This study aims to bridge the governance gap between national strategies (Macro) and agency operations (Micro) by developing a meso-level architecture for the SRIKANDI-SIKN ecosystem. An architectural artifact was produced on the basis of regulatory analysis and interviews as the methods of qualitative Design Science Research (DSR). Two formal events of expert synthesis, involving strategic policy makers and technical architects, were used to validate the artifact to create structural consistency and usefulness. This research extends enterprise architecture scholarship by formalizing public value, specifically fiscal efficiency and data sovereignty, as measurable design constraints within the EA6 Cube. Key findings reveal that the implementation of Hybrid API Gateway is a successful tool in system dualism management, whereas the Shared Responsibility model is also applied to address the accountability tension between central and local organizations. By establishing an auditable traceability chain, this study proves that meso-platforms serve as strategic levers for national alignment. The validated framework provides a rigorous pathway for transitioning from fragmented silos to integrated, value-driven digital ecosystems, supported by a measurable validation roadmap for national scalability and citizen-centric impact.